Spremljanje porabe kisika in frekvence srčnega utripa med simulacijo tekmovanja v kegljanju - Rauter, Samo (Šport (Ljubljana), 2016)
the purpose of the study was to estimate the level of effort during the simulation of 9-pin bowling competition. The study included 12 subjects (6 women and 6 men) all of which were from the 9-pin bowling national team of Slovenia. The study was divided into two parts. The first part of the study included Astrand's indirect method of determining the maximum oxygen consumption (6-minute sub-maximal cycling test). The second part of the study was the simulation of 9-pin bowling competition (120 throws). The results are compared and analysed according to the series of 10 throws each. We found that 9-pin bowling as a sport discipline can be estimated as a low intensity workout. The value of oxygen consumption during the simulation of competition ranging between 40-45% of maximum oxygen consumption values.
Keywords: effort; frekvenca srčnega utripa; heart rate; kegljanje; napor; nine pin bowling; oxygen consumption; poraba kisika; simulacija tekmovanja; simulation of competition; sport; šport